2021
DOI: 10.1083/jcb.202006040
|View full text |Cite
|
Sign up to set email alerts
|

Rab2 regulates presynaptic precursor vesicle biogenesis at the trans-Golgi

Abstract: Reliable delivery of presynaptic material, including active zone and synaptic vesicle proteins from neuronal somata to synaptic terminals, is prerequisite for successful synaptogenesis and neurotransmission. However, molecular mechanisms controlling the somatic assembly of presynaptic precursors remain insufficiently understood. We show here that in mutants of the small GTPase Rab2, both active zone and synaptic vesicle proteins accumulated in the neuronal cell body at the trans-Golgi and were, consequently, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…In neurons, the biogenesis of SVPs and DCVs involves complex sorting steps, followed by an association between the transport packet and the axonal motor, but how these processes are coordinated is unclear. 15, 58, 59 Particularly in cases where the same motor carries different cargo, specific mechanisms that promote its association with given cargos should exist. KIF1A/UNC-104 has a Pleckstrin Homology domain at its C-terminal tail that has been shown to bind PI(4,5)P2 and PI(4)P and is thought to be the main determinant in cargo recognition.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, the biogenesis of SVPs and DCVs involves complex sorting steps, followed by an association between the transport packet and the axonal motor, but how these processes are coordinated is unclear. 15, 58, 59 Particularly in cases where the same motor carries different cargo, specific mechanisms that promote its association with given cargos should exist. KIF1A/UNC-104 has a Pleckstrin Homology domain at its C-terminal tail that has been shown to bind PI(4,5)P2 and PI(4)P and is thought to be the main determinant in cargo recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Rab2 proteins, which are composed of Rab2b and Rab2a, are involved in the regulation of retrograde transport between the ER and the Golgi body [ 21 , 22 , 23 ]. They appear likely to regulate vesicle recycling around the Golgi body and autophagy in neuronal cells [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular matrix presented in the GO cellular component analysis of the hippocampus is involved in the regulation of the structure and function of the dendritic spine (Dityatev et al, 2010). Intracellular organelles, for example, the Golgi apparatus, are necessary for the formation of synaptic vesicles and thus play a dual role in synaptogenesis and neurotransmission (Götz et al, 2021). The cellular component analysis of the cerebral cortex revealed that DEGs were mainly involved in pre-and postsynaptic components.…”
Section: Discussionmentioning
confidence: 99%